Pengaruh Pertumbuhan Penjualan, Profitabilitas Dan Struktur Aktiva Terhadap Struktur Modal Pada Perusahaan Real Estate And Property Di Bursa Efek Indonesia - Lara Al-Ashry; Halkadri Fitra (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
This study aims to analyze the influence of (1) sales growth (2) profitability and (3) asset structure to capital structure (Debt to Equity Ratio) in real estate and property companies listed on the Indonesia Stock Exchange. this study is classified as causative research. The population in this study were all real estate and property companies listed on the Indonesia Stock Exchange in 2013-2017. The sample in this study was determined by purposive sampling based on the criteria of real estate and property companies listed on the IDX, companies that issued financial statements during the year of observation and companies that had net income during the year of observation. The sample in this study is 65. The type of data used is secondary data from the website www.idx.co.id. The analytical method used is multiple regression analysis using the SPSS program. The results of this study indicate (1) Sales growth has a negative and insignificant effect on the capital structure of real estate and property companies listed on IDX (2) Profitability has a positive and significant effect on the capital structure of real estate and property companies listed on the IDX (3) Asset structure has a positive and significant effect on the capital structure of real estate and property companies listed on the IDX.